Chiral surface plasmon-enhanced chiral spectroscopy: principles and applications. Issue 2 (7th January 2021) - Mu, Xijiao; Hu, Li; Cheng, Yuqing; Fang, Yurui; Sun, Mengtao
Abstract : In this review, the development context and scientific research results of chiral surface plasmons (SPs) in recent years are classified and described in detail. Abstract : In this review, the development context and scientific research results of chiral surface plasmons (SPs) in recent years are classified and described in detail. First, the principle of chiral SPs is introduced through classical and quantum theory. Following this, the classification and properties of different chiral structures, as well as the superchiral near-field, are introduced in detail. Second, we describe the excitation and propagation properties of chiral SPs, which lays a good foundation for the application of chiral SPs and their chiral spectra in various fields. After that, we have summarized the recent research results of chiral SPs and their applications in the areas of biology, two-dimensional materials, topological materials, analytical chemistry, chiral sensing, chiral optical force, and chiral light detection. Chiral SPs are a new type of optical phenomenon that have useful application potential in many fields and are worth exploring.